2017
DOI: 10.1186/s12889-017-4182-2
|View full text |Cite
|
Sign up to set email alerts
|

Views of Somali women and men on the use of faith-based messages promoting breast and cervical cancer screening for Somali women: a focus-group study

Abstract: BackgroundScreening rates for breast and cervical cancer for Muslim women in the United States are low, particularly for first-generation immigrants. Interpretations of the Muslim faith represent some of the barriers for breast and cervical cancer screening. Working to understand how faith influences breast and cervical screening for Somali women, and working with the community to identify and utilize faith-based assets for promoting screening, may lead to life-saving changes in screening behaviors.MethodsWe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 28 publications
7
36
0
Order By: Relevance
“…This fits well with an earlier study of Somalis that found Somalis are much more likely to make a health care decision after speaking with family members or friends (Lightfoot et al, 2016;Simmelink et al, 2013). Another recent study in this population that included both men and women found that men were encouraging of the women in their families in seeking cervical cancer screening once they were more aware of cervical cancer and screening (Pratt et al, 2017). Our findings are consistent with these and suggest that future interventions should include men in conversations about cervical cancer, screening, HPV, and HPV vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…This fits well with an earlier study of Somalis that found Somalis are much more likely to make a health care decision after speaking with family members or friends (Lightfoot et al, 2016;Simmelink et al, 2013). Another recent study in this population that included both men and women found that men were encouraging of the women in their families in seeking cervical cancer screening once they were more aware of cervical cancer and screening (Pratt et al, 2017). Our findings are consistent with these and suggest that future interventions should include men in conversations about cervical cancer, screening, HPV, and HPV vaccination.…”
Section: Discussionsupporting
confidence: 90%
“…This study supports the suggestion of a recent study that recommended developing a culturallytailored intervention to potentially increase participation in cervical cancer screening among Somali and other immigrant women in Norway [9]. A previous study that accounted for the views of Somali women and men demonstrated that faith-based messages can potentially reinforce the views of those already inclined to screening and encourage those with reservations [22]. Therefore, this study recommends the use of faithbased messages by engaging local imams who might dispel or at least mediate fatalistic understandings and address concerns about matters of modesty and sexuality as part of an intervention alongside other practical suggestions raised by the participants.…”
Section: Discussionsupporting
confidence: 88%
“…The finding that the research participants did not fully trust the doctors who might examine them is consistent with the findings of a previous study in which mistrust of the health system was based on reports from friends or relatives regarding problems that they had encountered [20,22]. Furthermore, the study findings also revealed a poor doctor-patient relationship, in which the participants perceived themselves as poorly received and their doctors as predominantly and problematically concerned about the number of children they chose to have, as a barrier to screening.…”
Section: Discussionsupporting
confidence: 87%
“…However, the nonprofit organization MN Community Measurement (2018) found that Somali immigrants ages 50–74 in Minnesota have a CRC screening rate of 27%, significantly below the statewide average (73%) and the screening rate for whites (74%). This agrees with a small yet consistent body of research showing lower rates of cancer screening and preventive services among African and other immigrant communities (Abdullahi et al, 2009; Consedine et al, 2011; Ghebre et al, 2015; Harcourt et al, 2014; Koo et al, 2012; Hurtado-de-Mendoza et al, 2014; Morrison et al, 2013; Morrison et al, 2012; Paszat et al, 2017; Pratt et al, 2017; Raymond et al, 2014; Redwood-Campbell et al, 2011; Sewali et al, 2015; Shankar et al, 2016; Shen et al, 2018; Upvall et al, 2009). For example, Koo et al (2012) found that physicians were less likely to recommend CRC screening to immigrant patients and that the ethnicity of both the provider (independent of medical training) and the patient influenced screening rates.…”
Section: Introductionsupporting
confidence: 89%
“…Barriers to screening uptake included access (e.g., insurance, transportation) and psychosocial concerns (e.g., shame). Recent research by Pratt et al (2017) on screening for breast and cervical cancer among Somali women revealed that faith-based messaging substantially improved screening uptake. Sewali and colleagues (2015) found that Somali men generally lacked knowledge about cancer screening and that most believed they were less at risk because of their Islamic faith.…”
Section: Introductionmentioning
confidence: 99%